The effect of some environmental factors on the abundance and distribution of annelid worms from Shatt Al-Arab, Basra, southern Iraq - Abed , Hassan Bader; Al-Abbad, Murtatha Y.; Al-Qarooni, Imad H. (Iraqi Journal of Aquaculture, 2023)
The present study aims at diagnosing the species of Annelida in the sediment of Shatt Al-Arab and studying their density. The study period and the sample collection starts from January 2021 up to May 2021. Nine stations lying on Shatt Al-Arab at Basrah district were chosen starting from Qurna station northward to Al-Fao station southward. The study included measuring some environmental factors of water and sediments. Water temperature ranged between 9-19, 7.2-8.6 for pH, 5.8-9.1 Mg/ltr for dissolved oxygen, 2.1-29.5 ppt for salinity concentrations. In sediments, the percentage of TOC was 0.25-1.03 %. Three species of Annelida were diagnosed in the study stations, two of them belong to Namalycastis indica, Dendronereides heteropoda. The third species belongs to Limnodrilus hoffmeisteri. The density of the diagnosed Annelida during the study period were recorded. It ranged between 1550-3709 individual/m2 for Polychaeta species while for L. hoffmeisteri, the density ranged between 2159-8885 individual/m2. The distribution of diagnosed Annelida into longitudinal classes was studied and it recorded the least appearance rates of the D. heteropda species in the 40-50 mm class in most of the study stations while the highest appearance was recorded for the 1-10mm class in a number of stations. N. indica has recorded the least appearance rates for 40-50 class mm in most of the study stations, however, it has recorded the highest rates of appearance for 30-40 mm class in four stations. For the L. hoffmeisteri species, the least rate of appearance was recorded for 18-21 mm class in some stations, while the highest rate of appearance was recorded for 3-6mm in many stations. The statistical analysis showed that temperature, pH, and salinity are directly related to the density of both species of Annelida while the dissolved oxygen is directly related to the density of L. hoffmeisteri (r=0.470) and inversely with Polychaeta species (r=-0.094).